Managing Volunteers Effectively - McSweeney, Phil.; Alexander, Don. (Aldershot : Arena, 1996)
This work offers practical advice to those who are taking up the responsibility of managing volunteers. It covers the changes that society is undergoing, whereby volunteers and community care have become important; organizational culture; the special needs of volunteers; and teamwork.
Includes bibliographical references and index.
Keywords: Volunteers; Voluntarism -- Management; Voluntarism -- Personnel management